P-BN24 Quality assessment of online patient information on upper gastrointestinal endoscopy using the Modified Ensuring Quality Information for Patients (EQIP) tool. (16th December 2021) - Miller, Gillian; Chien, Siobhan; Huang, Ivory; Cunningham, Danielle; Carson, Daniel; Gall, Lewis; Khan, Khurram
Abstract: Background: Online resources are rapidly becoming patients' primary source of healthcare information due to the Internet's ease of access. The availability of high-quality online information is paramount to improving patient education and clinical outcomes. Upper gastrointestinal (UGI) endoscopy is the gold standard investigation for UGI symptoms, yet little is known regarding the quality of patient oriented websites. This study aims to analyse the quality of online patient information on UGI endoscopy using the modified Ensuring Quality Information for Patients (EQIP) tool. Methods: A systematic review was conducted using 10 search terms. The top 100 websites for each term identified using Google search were assessed using the modified EQIP tool (score 0-36). Sub-analysis was performed on high-scoring websites. Websites for medical professional use or containing video and marketing content were excluded. Results: 378 websites were eligible for analysis. The median modified EQIP score for UGI endoscopy was 18/36 (IQR 14-21). Median EQIP scores for the content, identification and structure domains were 8/18, 1/6 and 9/12, respectively. Websites produced by government health departments and NHS hospitals had a higher modified EQIP score (p = 0.007). Complication rates were included in only 20.4% of websites. High-scoring websites were significantly more likely to provide balanced information on risks and benefits (94.6% vs. 34.4%; p < 0.001). Conclusions: The current quality of online patient information on UGI endoscopy is limited, with minimal information available on risks of the procedure, potentially hindering patients' ability to make informed healthcare decisions. There is an immediate need for high-quality online resources to improve patient education.